Identification and validation of the role of matrix metalloproteinase-1 in cervical cancer - Tian, Run (Int J Oncol, 2018)
Lymph node (LN) metastasis at an early stage of cervical cancer is often an indicator of poor prognosis and is critical for subsequent adjuvant therapy. The current study aimed to identify aberrant gene signatures and biomarkers of metastasis for patients with cervical cancer. RNA-sequencing data of 132 LN negative (N0) and 60 LN positive (N1) cervical cancer samples obtained from The Cancer Genome Atlas database were analyzed. Differentially expressed genes were identified using R packages 'edgeR' and 'limma'. Kyoto Encyclopedia of Genes and Genomes pathway enrichment and Gene Set Enrichment Analysis (GSEA) were conducted. The GSE9750 dataset obtained from Gene Expression Omnibus was analyzed to identify genes that are persistently aberrantly expressed during the development of cervical cancer. The peroxisome proliferator-activated receptor (PPAR) signaling pathway was screened out to be significant during LN metastasis. In the two analyzed datasets, 11 genes were aberrantly expressed, while matrix metalloproteinase 1 (MMP1) was the only gene that was persistently overexpressed. Cell viability, wound healing and Transwell assays were performed to evaluate the effects of MMP1 knockdown in cervical cancer cell lines, and the expression of epithelial mesenchymal transition (EMT) markers was detected. Finally, the clinical significance of MMP1 was investigated. The current study identified that MMP1 was overexpressed and the PPAR signaling pathway was associated LN metastasis in patients with cervical cancer. Following knockdown of MMP1, the proliferation, migration and invasion of cervical cancer cell lines were weakened, the expression of epithelial marker E-cadherin was increased, and the expression of metastasis-associated gene vimentin was decreased. MMP1 was an independent prognostic factor for cervical cancer. The current study indicated that MMP1 has a key role in the regulation of cervical tumor growth and LN metastasis via EMT to a certain extent. The results suggest that MMP1 may be a biomarker for LN metastasis of cervical cancer, and further validation should be performed.